Conducting polymer nanocomposite-based supercapacitors - Liew, Soon Yee; Walsh, Darren A.; Chen, George Z. (Springer, 2016)
The use of nanocomposites of electronically-conducting polymers for supercapacitors has increased significantly over the past years, due to their high capacitances and abilities to withstand many charge-discharge cycles. We have recently been investigating the use of nanocomposites of electronically-conducting polymers containing conducting and non-conducting nanomaterials such as carbon nanotubes and cellulose nanocrystals, for use in supercapacitors. In this contribution, we provide a summary of some of the key issues in this area of research. This discussion includes some history, fundamental concepts, the physical and chemical processes involved, and the challenges that these nanocomposite materials must overcome in order to become technologically viable. Due to space limitations, this is not a complete review of all the work that has been done in this field and we have focused on common themes that appear in the published work. Our aim is that this chapter will help readers to understand the advantages and challenges involved in the use of these materials in supercapacitors and to identify areas for further development.